Pengaruh Jumlah Penduduk dan Inflasi terhadap Kemiskinan di Indonesia (Studi Kasus 34 Provinsi) - Rizkina, Azka; Qadafi, Muammar; Asnita, Yuni; Afriana; Ariga, Hijrah Purnama Sari (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study examines the effect of population and inflation on poverty in Indonesia (Case Study of 34 provinces in Indonesia). Using panel data, namely using time series and cross-section data. Where the time series data used is annual data from 2015 - 2024, with a total n of 340. While the cross section in this study covers 34 provinces in Indonesia. The method used is the panel data regression method, so the results of this study show that when viewed from the results of the t-test, the population variable has an effect on poverty. While the inflation variable has no effect on poverty. However, when viewed simultaneously (f test) the population and inflation variables together have an effect on poverty in Indonesia.